Entropy generation due to Laminar Natural Convection over a Heated Rotating Cylinder - A.K. Abu-Hijleh, Bassam (1999)
Entropy generation due to laminar mixed convection from an isothermal rotating cylinder was calculated numerically. The study was conducted for three cylinder radii and covered wide ranges of Reynolds number and buoyancy parameter. Entropy generation increased as the Reynolds number and buoyancy parameter increased. Entropy generation decreased as the cylinder radius increased. For the same combination of Reynolds number and buoyancy parameter, entropy generation was mainly due to thermal effects at small cylinder radii and due to viscous effects at large cylinder radii.